ASSESSMENT OF THE EFFECTIVENESS OF DIGITAL LEARNING APPROACHES IN PHYSICS LABORATORY INSTRUCTION (Eureka Journal of Education & Learning Technologies, 2026)
This study investigates the pedagogical effectiveness of integrating digital learning approaches into physics laboratory instruction. In contemporary higher education, the adoption of virtual laboratories, simulation-based learning environments, and interactive digital tools has become increasingly significant for enhancing students’ conceptual understanding and practical skill development. The research explores how such technologies influence students’ academic performance, experimental competence, and independent learning capacity. The findings indicate that digitally supported laboratory instruction provides a more engaging and cognitively effective learning environment compared to conventional laboratory teaching practices.
Keywords: Physics education, laboratory instruction, digital learning environment, virtual experimentation, simulation-based learning, interactive pedagogy, educational technology, competency development.